2011
DOI: 10.1161/circulationaha.110.989129
|View full text |Cite
|
Sign up to set email alerts
|

Myotomy After Previous Coronary Artery Bypass Grafting for Treatment of Myocardial Bridging

Abstract: A 57-year-old man with a long history of frequent chest pain was admitted to our cardiac center. Four years ago, he underwent coronary artery bypass grafting (CABG) with the left internal mammary artery (LIMA) to the distal segment of the left anterior descending coronary artery (LAD) grafting for myocardial bridging (MB) in LAD despite having ␤-blockers and calcium channel blockers. However, the patient still had recurrent angina within 3 months after the operation. ECG showed negative T wave in leads V1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 4 publications
1
10
0
2
Order By: Relevance
“…Most publications regarding surgical treatment of myocardial bridging are simple case reports [25,26]. Our experience suggests that myocardial bridge unroofing in HCM patients presenting with angina may afford greater relief of their symptoms than myectomy alone.…”
Section: Commentmentioning
confidence: 81%
“…Most publications regarding surgical treatment of myocardial bridging are simple case reports [25,26]. Our experience suggests that myocardial bridge unroofing in HCM patients presenting with angina may afford greater relief of their symptoms than myectomy alone.…”
Section: Commentmentioning
confidence: 81%
“…As such, failure of CABG to improve symptoms has been associated with the need for subsequent unroofing. 39 Unroofing definitively corrects the anatomic defect, thereby improving flow and relieving the source of myocardial ischemia, 40 and can be performed via sternotomy on or off cardiopulmonary bypass or via a minimally invasive approach. [41][42][43][44][45]…”
mentioning
confidence: 99%
“…It has been acknowledged that MB can influence dynamic nature of coronary arteries. Furthermore, some studies showed that myocardial vessel compression existed not only in systole but was also persistent during diastole [13]. In some studies, and case reports, it was associated with cardiac ischemia, angina, arrhythmias, or even sudden death [14,15].…”
Section: Discussionmentioning
confidence: 99%